Carabo-Cone, Dalcroze, Kodály, and Orff Schulwerk Methods: An Explanatory Synthesis of Teaching Strategies in Music Education - Almighty C. Tabuena (International Journal of Asian Education, 2021)
This study emphasizes findings from literature reviews that aimed to describe and present the current teaching strategies in Music education. These teaching strategies are one of the needed primary skills of Music teachers to address the learning challenges, competencies, and diverseness of the existing curriculum, help them to explore the needs of the students, and give them a framework of what could be the best and appropriate strategy in delivering a lesson. This study employed a descriptive method to gather information about present conditions through a library method and literature review. The data were analyzed using explanatory synthesis. Based on the literature review, the researcher identified four well-known teaching strategies in Music education: the Carabo-Cone Method, Dalcroze Method, Kodaly Method, and Orff Schulwerk Approach. The researcher used four criteria in synthesizing reviews such as the proponent, foundation, philosophy, and methodology. Conclusion of the results and discussions, the four teaching strategies also varied in four indicators, yet similarly focused on using the senses for holistic growth and development and providing all students with the opportunity to be successful. The quality of education depends mostly on the part of the teacher. The different Music teaching strategies serve as a guide to fulfilling the purpose satisfactorily that a teacher and a student needs. It is recommended to analyze its implications towards different modes of learning as global education facing numerous challenges in terms of economic crisis, pandemic, and educational incapability and inequalities that could affect the educational system.